Correlation Between Spirituality and Anxiety Levels in Patients with Cancer - Rosmiati; Munir, Nur Wahyuni; Suhermi (Bantayang Omni Cendekia, 2025)
Background: Cancer is one of the non-communicable diseases that causes significant anxiety in patients, both during the diagnosis process and treatment. This anxiety can affect the patient's quality of life, so a holistic approach is needed in treatment, including aspects of spirituality. Objective: The aim of this study was to identify the correlation between spirituality and anxiety levels of patients with cancer. Methods: This study was conducted quantitatively with a cross-sectional approach using sociodemographic questionnaire, Spiritual Well-Being Scale (SWBS), and Hamilton Anxiety Rating Scale (HARS). This study involved 60 cancer patients in a hospital in Makassar. Results: Majority of respondents did not experience anxiety, amounting to 27 respondents (46.7%) and over half respondents had good spirituality level, which accounting for 31 (51.7%) respondents. In addition, the Chi Square test analysis obtained a p-value of 0.001, indicating that there was a significant correlation between spirituality and anxiety level of respondents. Conclusion: There is a significant relationship between spirituality and anxiety levels of patients with cancer. Therefore, the integration of spiritual support in cancer care, especially chemotherapy and palliative patients, is highly recommended to improve the psychological well-being of patients.